Aspiration thrombectomy for posterior circulation stroke: A systematic review and meta-analysis - Sheng, Kevin; Tong, Marcus (Asian Journal of Neurosurgery, 2020)
Purpose: This study aims to analyze the efficacy of aspiration thrombectomy for large vessel occlusion of the posterior circulation, with an emphasis on comparison with stent retriever thrombectomy. Methods: A systematic review and meta-analysis were performed to analyze the outcomes of aspiration thrombectomy for acute posterior circulation stroke. For those studies that included data for both aspiration and stent-retriever thrombectomy, we additionally performed a second meta-analysis comparing their outcomes against each other. Results: A total of 17 articles were included. For the primary outcomes, the weighted pooled rate of mortality was 26.71% (95% confidence interval [CI] 19.35%–34.71%), modified Ranking Score (mRS) 0–2 at 3 months was 36.71 (95% CI 32.02%–41.52%), and successful recanalization 89.26% (95% CI 83.12%–94.31%). Primary stent retriever thrombectomy was inferior to primary aspiration thrombectomy for the outcomes of successful recanalization (odds ratio [OR] 0.57, 95% CI 0.36–0.91, P = 0.018), complete recanalization (OR 0.65, 95% CI 0.42–0.1.00, P = 0.048), procedure time (mean difference 28.17, 95% CI 9.47–46.87), and rate of embolization to new territory (OR 5.01, 95% CI 1.20–20.87, P = 0.027). No significant difference was seen for other outcomes. Further subgroup analysis suggests that for the outcome of recanalization, this may be dependent on the availability of second-line stent retriever thrombectomy. Limitations: The included studies were observational in nature. There was unresolved heterogeneity in some of the outcomes. Conclusions: There was no statistically significant difference seen for the primary outcomes of mortality and favorable outcome (mRS score 0–2) at 3 months. While superior rates of successful recanalization, complete recanalization, faster procedural time, and improved safety profile for primary aspiration thrombectomy were seen compared to primary stent retriever thrombectomy, this did not translate into superior clinical outcomes.
Keywords: Aspiration; posterior circulation; stent retriever; stroke; thrombectomy